Praktik Gharar dalam Promosi TikTok Shop: Analisis Konten Digital Berbasis Fiqih Muamalah - Echa Ayu Safitri; Fadhilah Yulandari; Wulan Permata Sari; Muhammad Fariq Heemal Attruk (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study analyzes gharar practices in TikTok Shop promotions through a fiqh muamalah approach integrated with empirical findings on live-streaming commerce and urgency marketing. The data shows that uncertainty arises not only in the object of the contract through discrepancies in the identity and specifications of goods, but also in pricing through non-transparent discounts and price changes at checkout, as well as in transaction mechanisms such as limited stock claims and inconsistent COD promotions. Using the Stimulus–Organism–Response framework, this study interprets that affective pressure, arousal, and fear of missing out accelerate decision-making, thereby affecting the quality of tarāḍī in contracts. Normative analysis classifies the spectrum of gharar from yasīr to fāḥish based on the affected contract elements and the level of information distortion. Unlike gharar studies that generally focus on modern financial instruments, this study places digital promotions as the locus of evaluating the validity of contracts in social commerce, and affirms the preventive function of fiqh muamalah in assessing the transparency and fairness of platform-based transactions.